Study on transformation of zerumbone with fatty acid hydrazides - Truong, Vuong Van; Nam, Pham Duy; Thanh, Nguyen Dinh; Huong, Van Ngoc; Thuy Lien, Trinh Thi; Chinh, Luu Van (Vietnam Journal of Chemistry, 2015)
Zerumbone was isolated from several plant species of the Zingiberaceae family that have shown many potential biological activities, such as antiproliferative, antioxidative, anti-inflammatory, and anticancer activities. Due to these biological effects, many scientists have tried to synthesize zerumbone derivatives and evaluate their bioactivities. In this paper, we report the synthesis of nine new zerumbone derivatives by the <a href="http://www.google.com.vn/url?sa=t&rct=j&q=&esrc=s&source=web&cd=12&cad=rja&uact=8&ved=0CHQQFjAL&url=http%3A%2F%2Fwww.daviddarling.info%2Fencyclopedia%2FC%2Fcondensation_reaction.html&ei=52SeU6SyB8zs8AXX7YLYDQ&usg=AFQjCNGBj1HxcCRrcdUrV3sCXcrINBLd3A&sig2=nCN_JYDZhgxRXkAY4aYGjw&bvm=bv.68911936,d.dGc">condensation of zerumbone and zerumbone oxide with fatty acid hydrazides. The structure of these compounds has been confirmed by 1H NMR, 13C NMR and FT-ICR-MS spectroscopic data.